1997
DOI: 10.1210/mend.11.11.0010
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Mitogen-Activated Protein/ERK Kinase (MEK)1 and MEK2 and Activation by a Ras-Independent Mechanism

Abstract: Mitogen-activated protein (MAP)/ERK kinase (MEK)1 and MEK2 are the upstream activators of the MAP kinases, ERK1 and ERK2. MEK1 and MEK2 are approximately 85% identical in sequence but have unique inserts in their C-terminal domains. MEK isoform-specific antibodies were used to examine expression and regulation of each enzyme. MEK1 and MEK2 were expressed in approximately equal amounts in several cell lines; in some, MEK1 was present in slight excess. Activation of tyrosine kinase-containing receptors, heterotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 44 publications
1
18
0
1
Order By: Relevance
“…Most clear, MEK1 activity is required; pharmacological inhibitors as well as an inhibitory mutant of MEK1 block ERK1/2 activation, consistent with the finding that MEK1 but not MEK2 is responsive to glucose (9). A small G protein, most likely Ras, is also required, based on the inhibitory effects of a dominant-interfering Ras mutant and of an N-terminal fragment of Raf1, which is thought to act by se- questering activated Ras, preventing it from binding to endogenous Raf proteins.…”
Section: Discussionsupporting
confidence: 78%
“…Most clear, MEK1 activity is required; pharmacological inhibitors as well as an inhibitory mutant of MEK1 block ERK1/2 activation, consistent with the finding that MEK1 but not MEK2 is responsive to glucose (9). A small G protein, most likely Ras, is also required, based on the inhibitory effects of a dominant-interfering Ras mutant and of an N-terminal fragment of Raf1, which is thought to act by se- questering activated Ras, preventing it from binding to endogenous Raf proteins.…”
Section: Discussionsupporting
confidence: 78%
“…We could show that this p21 cip1 induction resulted in a senescencelike phenotype. Under normal conditions it had been shown that only MEK1 is activated in response to serum stimulation (19) and that this transient activation is sufficient to provide proliferative signals but fails to induce a sustained expression of p21 cip1 and growth arrest (14). In this context we could provide evidence that MEK2 can complement for MEK1 in response to serum stimulation but causes sustained and stronger ERK activity.…”
Section: Forced Activation Of Mek2 Results In a Senescence-like Phenomentioning
confidence: 73%
“…When MEK1 activity became prominent as in the MEK2 knock down, the resulting ERK signaling provided proliferative signals. Serum stimulation indeed preferentially induces MEK1 activity in several cell types (19). Therefore, we suggest a model in which the specific activation of either MEK1 or MEK2 is part of the cellular system that enables the mitogenic switch between inhibition and enhancement of cell proliferation.…”
Section: Forced Activation Of Mek2 Results In a Senescence-like Phenomentioning
confidence: 81%
See 1 more Smart Citation
“…1 utilizing, as a measure of ERK1 and ERK2 activation, immunoblotting with anti-Active MAPK antisera. Labeling by this antibody has been demonstrated to closely correlate with kinase activity (34). Immunodetectable levels of active ERK1 and ERK2 reached maximum within 5 to 10 min of stimulation with IL-5.…”
Section: Time Course Of Erk1 and Erk2 Activation By Il-5-asmentioning
confidence: 92%